TOC: Lightweight Event Tracing Using Online Compression for Networked Embedded Systems. (1st November 2015) - Cao, Chenhong; Liu, Wen; Dong, Wei; Bu, Jiajun
Abstract : Many trace-based diagnostic techniques have been proposed for abnormal detection and fault diagnosis in networked embedded systems such as wireless sensor networks (WSNs). Event tracing is a nontrivial task for resource-constrained embedded devices. Existing tracing approaches employ compression algorithms to reduce the trace size. However, these approaches either are inapplicable or perform poorly. In this paper, we propose TOC, a novel event tracing technique using online compression. TOC combines periodical pattern mining and efficient token assignment, effectively reducing the trace size with acceptable execution overhead. We implement TOC based on TinyOS 2.1.2 and evaluate its effectiveness by case studies in sensor network applications. Results show that TOC reduces the trace size by 52.2%, compared with LIS—a state-of-the-art event tracing method.